2021
DOI: 10.1136/bmjopen-2021-054681
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intravenous S(+)-ketamine for acute postoperative pain in adults: study protocol for a multicentre, randomised, open-label, positive-controlled, pragmatic clinical trial (SAFE-SK-A trial)

Abstract: Introduction Postoperative pain remains incompletely controlled for decades. Recently, multimodal analgesia is emerging as a potential approach in the management of postoperative pain. Therein, S(+)-ketamine is appealing as an adjuvant drug in multimodal analgesia due to its unique pharmacological advantages. This pragmatic clinical trial (SAFE-SK-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Then, a study found that high doses of S‐ketamine might induce reversible neuropsychiatric side effects, such as delirium and dizziness; on the contrary, these side effects of low S‐ketamine doses are well tolerated, reversible, and of low incidence. 37 This founding is consistent with ours.…”
Section: Discussionsupporting
confidence: 93%
“…Then, a study found that high doses of S‐ketamine might induce reversible neuropsychiatric side effects, such as delirium and dizziness; on the contrary, these side effects of low S‐ketamine doses are well tolerated, reversible, and of low incidence. 37 This founding is consistent with ours.…”
Section: Discussionsupporting
confidence: 93%
“…The possible mechanisms by which esketamine can assist opioids with analgesic effect were as follows: continuous infusion of subanesthetic doses of esketamine can further reduce the hyperactivation of the ascending nociception conduction pathway and reduce the release of pain-causing substances such as dyrophins in the spinal cord, [ 9 ] it may be related to the role of the NMDAR in morphine tolerance, [ 10 ] it has been reported that the effect of small-dose esketamine on NMDAR should not be considered as “analgesia,” but be considered as “anti-pain allergy,” “anti-abnormal pain” and “protective effect against tolerance.” [ 11 ]…”
Section: Discussionmentioning
confidence: 99%